Recent advances in perovskite solar cells: efficiency, stability and lead-free perovskite - Yang, Shida; Fu, Weifei; Zhang, Zhongqiang; Chen, Hongzheng; Li, Chang-Zhi (Journal of materials chemistry. A, Materials for energy and sustainability, 2017)
With the rapid growth of efficiency from 3.8% to 22.1% in recent years, perovskite solar cells (PVSCs) have drawn significant attention of researchers from both academia and industry. However, significant barriers remain standing in the pathway of PVSC advancement. To develop high-efficiency and stable devices as well as environmentally benign perovskites is critical, yet challenging aspects remain in PVSC research. In this review article, we focused on the recent advances in related subjects. The approaches for high-efficiency PVSCs have been introduced and then the instability issues and lead-free perovskite have been discussed. Finally, the conclusion along with brief perspectives has been provided on further advancing PVSCs towards use in efficient and stable solar-to-electricity technologies. In this review, we first highlighted recent progress in high-performance perovskite solar cells (PVSCs) with a discussion of the fabrication methods and PVSCs-based tandem solar cells. Furthermore, the stability issue of PVSCs and strategies to improve material and device stability have been discussed, and finally, a summary of the recent progress in lead-free perovskites has been presented.